2014
DOI: 10.1590/bjb.2014.0086
|View full text |Cite
|
Sign up to set email alerts
|

Preferential prey selection by Desmodus rotundus (E. Geoffroy, 1810, Chiroptera, Phyllostomidae) feeding on domestic herbivores in the municipality of São Pedro - SP

Abstract: In order to verify possible preferential prey selection by Desmodus rotundus feeding on domestic herbivores in the Municipality of São Pedro (São Paulo, Brazil), vampire bat attacks were surveyed at rural properties where domestic herbivores were being raised and attack frequencies of D. rotundus on the total herd and on different species were calculated. The analysis found that the most frequently attacked herbivores were cattle and horses. The chi-square test (χ 2 ), with a significance level of 5% corrobora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
(18 reference statements)
2
8
0
1
Order By: Relevance
“…The diet of vampire bats comprises predominantly domestic animals, including chicken, bovine and equine cattle, and dogs, so that studies detecting the presence of wild animals are rare (Costa & Esbérard, 2011;Mialhe, 2014;Bobrowiec et al, 2015). Bobrowiec et al (2015) analyzed samples of 48 vampire bats (D. rotundus and D. youngi) in central-western Amazon using molecular data and native animal in the diet of the two species were not recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diet of vampire bats comprises predominantly domestic animals, including chicken, bovine and equine cattle, and dogs, so that studies detecting the presence of wild animals are rare (Costa & Esbérard, 2011;Mialhe, 2014;Bobrowiec et al, 2015). Bobrowiec et al (2015) analyzed samples of 48 vampire bats (D. rotundus and D. youngi) in central-western Amazon using molecular data and native animal in the diet of the two species were not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Its diet is mainly composed of mammal blood, and it feeds secondarily on birds, and, eventually, human blood (Turner, 1975;Schneider et al, 2001Schneider et al, , 2009). Despite a good documentation of bats feeding on animals, in particularly domesticated animals, such as bovine cattle (Dalquest, 1955;Voigt & Kelm, 2006;Mialhe, 2014), the data on bat diet in natural environments using wild preys are scarce.…”
mentioning
confidence: 99%
“…This work was supported by funding assigned to Javier Laborde (INECOL/200030-10281), with which fieldwork of this project was carried out. CONACyT Mexico provided a Retention scholarship to Beatriz Bolívar (No. 2014 PCI-1054.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Several authors have documented that D. rotundus can inhabit different types of man-made habitats, such as agroforestry plots, silvopastoral systems, pastures and secondary forests, and the species has also been found in patches of old-growth or undisturbed forests (Kalko andHandley 2001, García-Morales et al 2013). Some studies have reported an increase in the abundance of this bat species in tropical areas of America, and it has been linked to the increase in the number of livestock herds available as its food source (Medellín et al 2000, Mialhe 2014, Bobrowiec et al 2015. The presence of D. rotundus has been constantly monitored through animal health programs because this bat species is the only known vector of bovine paralytic rabies and may cause significant economic losses (Mayen 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation